PENGGUNAAN MULTIMEDIA INTERAKTIF PADA PEMBELAJARAN DI MADRASAH IBTIDAIYAH - Suhendra, Ade (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2019)
This writing describe about using learning media based interactive multimedia on Primary Education by using Macromedia Flash. Using Macromedia Flash will be developedÂ  the implementation ofÂ  the quality learning. Based on this research, we find that after using Macromedia Flash, the students enjoyed the the learning and improve their motivation to study hard. Therefore, learning quality is improved by using Macromedia Flash.